Forms Of Legal Certainty Regarding The Status Of Workers Due To Company Separation (SPIN-OFF) - Junaedi Junaedi (Departement of Mathematics Education, 2022)
The legal certainty referred to in this article is legal certainty regarding the status of workers as a result of the spin-off of the company. This legal certainty is the enforcement of the implementation of the Employment Law and the Limited Liability Company Law. According to Sudikno Mertukusumo, legal certainty is a guarantee that the law must be implemented in a good manner. This article was written using a qualitative method with an approach to existing legislation and legal doctrine to examine phenomena or changes that occur in society, one of which is the separation of companies and the legal consequences this causes for workers.